PERAN ORANG TUA TERHADAP PEMEROLEHAN BAHASA ANAK USIA 3 TAHUN - Sry Rahayu, Isma; Nuraini , Nuraini; Jumiati, Jumiati; Zain, Suardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the role of parents in the language acquisition of a three-year-old child as a crucial phase in cognitive and communicative development. The research aims to analyze the forms of parental involvement and their impact on children’s language acquisition within the family environment. This study employs a qualitative approach with a descriptive method. The subjects consist of two parents who have a three-year-old child. Data were collected through in-depth interviews focusing on communication patterns, language stimulation, parental responses to children’s utterances, language modeling, and the emotional environment within the family. Data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that parental roles are manifested through intensive and two-way communication, consistent and contextual language stimulation, positive and non-judgmental responses, and appropriate language modeling. A supportive emotional environment further strengthens the child’s language acquisition process. The impact of these roles is reflected in the child’s expanded and contextual vocabulary, the ability to construct simple yet structured sentences, the capacity to understand complex instructions, and increased confidence in communication. The involvement of both parents also provides varied linguistic input that enriches the child’s language experience. These findings highlight that consistent interaction, quality language stimulation, and emotional support within the family are key factors in successful early childhood language acquisition. Future research is recommended to involve a larger number of participants and consider broader socio-cultural factors.